Influence of Hyperglycaemia and CRP on the Need for Mechanical Ventilation in Guillain-Barré Syndrome - Štětkářová, Ivana; Ehler, Edvard; Židó, Michal; Lauer, David; Polák, Jan; Keller, Jiří; Peisker, Tomáš (Frontiers in Neurology, 2022)
Objectives: Elevated blood glucose and CRP (C-reactive protein) are usually related to a worsened clinical outcome in neurological diseases. This association in Guillain-Barré syndrome (GBS) has been studied rarely. We tried to analyse if hyperglycaemia and CRP at admission may influence the outcome of GBS, including mechanically ventilated (MV) patients. Methods: We retrospectively studied 66 patients (40 males, 19-93 years, average 56 yrs.) without diabetes mellitus and free of corticoid treatment, who fulfilled the clinical criteria for diagnosis of GBS. Hyperglycaemia (the level of fasting plasma glucose, FPG) was defined as blood glucose level >5.59 mmol/L according to our laboratory. CRP >5 mg/L was considered as an abnormally elevated value. Results: At admission, 32 GBS patients (48%) had hyperglycaemia according to FPG level. A severe form of GBS (>4 according to Hughes GBS scale) was observed in 17 patients (26%); and 8 of them (47%) had hyperglycaemia. Fourteen patients (21%) were MV, and in 10 of them (71%) hyperglycaemia was present. CRP was significantly increased in MV patients. The linear model revealed a significant relationship between CRP and glycemia (p = 0.007) in subjects without MV (p = 0.049). In subjects with MV the relationship was not significant (p = 0.2162, NS). Conclusion: In the acute phase of GBS at admission, hyperglycaemia and higher CRP occur relatively frequently, and may be a risk factor for the severity of GBS. Stress hyperglycaemia due to impaired glucose homeostasis could be one explanation for this condition.